2020
DOI: 10.24017/science.2020.1.3
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Stock Price Prediction Using Gradient Boosting Machine with Feature Engineering (GBM-wFE)

Abstract: The prediction of stock prices has become an exciting area for researchers as well as academicians due to its economic impact and potential business profits. This study proposes a novel multiclass classification ensemble learning approach for predicting stock prices based on historical data using feature engineering. The proposed approach comprises four main steps, which are pre-processing, feature selection, feature engineering, and ensemble methods. We use 11 datasets from Nasdaq and S&P 500 to ensure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Gradient Boosting was adopted by Nabi (2020) to predict the stock market movement with a feature engineering variation (GB-FE) from historical data for the Nasdaq and S&P500. A mean square error (MSE) of 0.041% is attained, proving its effectiveness.…”
Section: Relative Strength Indexmentioning
confidence: 99%
“…Gradient Boosting was adopted by Nabi (2020) to predict the stock market movement with a feature engineering variation (GB-FE) from historical data for the Nasdaq and S&P500. A mean square error (MSE) of 0.041% is attained, proving its effectiveness.…”
Section: Relative Strength Indexmentioning
confidence: 99%
“…The work of Vijh et al (2020) has shown that popular machine learning models such as random forests and neural networks are efficient in predicting US stock prices. Nabi et al (2020) and Yang et al (2020) also tried several popular machine-learning approaches to find the superiority of the Gradient Boosting models among others in stock price forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging as one of the most contemporary machine learning techniques, gradient boosting has shown success in various areas including stock price prediction (Nabi et al, 2020), traffic speed forecast (Zhan et al, 2020), Alzheimer diagnosis (Liu et al, 2020) and health monitoring systems (Tahmassebi et al, 2020). In addition to this, gradient boosting has recently shown promising use in several engineering problems such as automatic detection of cracks from concrete surface (Chun et al, 2021), structural damage assessment for proper maintenance (Chun et al, 2020a, b), prediction of undrained shear strength (Zhang et al, 2021) and safety evaluation of steel trusses (Truong et al, 2020), which opens new avenue in modeling engineering problems including seismic damage assessment of structures.…”
Section: Introductionmentioning
confidence: 99%